Influence of defects on damage tolerance of Metal-Injection-Molded β titanium alloys under static and dynamic loading. (20th October 2022) - Xu, Peng; Ebel, Thomas; Pyczak, Florian; Willumeit-Römer, Regine; Yu, Sen
ABSTRACT: The β titanium alloys are key materials in lightweight and biomedical applications, due to the combination of excellent biocompatibility and mechanical properties. However, the Binder-based Powder Technologies such as Metal-Injection-Molding (MIM), Binder-Jetting and Fused-Filament-Fabrication, normally introduce three major processing-related defects in the as-sintered Ti-parts: (i) residual porosity, (ii) high impurity level and (iii) coarse-grained structure. The previous studies revealed that these processing defects invariably tend to be even more severe in β titanium alloys than in α/β Ti-6Al-4V alloy, all fabricated by powder metallurgical route. In this work, these processing defects and their likely origins in MIM β titanium alloys are analysed. Furthermore, the influence of these defects on damage tolerance and fracture mechanisms of MIM β titanium alloys under either static or dynamic loading is investigated. Based on the studies, strategic technical improvements in the processing to improve the reliability of MIM β titanium alloys products are proposed.